The shari'ah objectives and their implications for non-Muslim minorities: the case of Malaysia - Amanullah, Muhammad (The Other Press, 2015)
Islam is considered to be the only complete code of life available for the whole human kind on this planet. It comprises principles and rulings for all aspects of this worldly life and life hereafter, which are combinedly called SharÊÑah or Islamic Shari`ah. The Law Giver, i.e. Allah (SWT) did not provide these principles and rulings of the Shari`ah without intending important objectives for them, which are crucial for righteous, honorable, dignified and just survival of human beings. According to their effect on a society and individuals, these objectives are divided into three categories: 1. Essentials (ÌarËriyyÉt), i.e. aspects on which human beings’ religious and worldly life depend, without which human life in this world will be defective and disorder will spread among them, their happiness will disappear permanently, and punishment will be inflicted to them in their life hereafter. 2. Necessities (ÍÉjiyÉt), i.e. aspects without which human life will not be defective, but they are needed by them to remove hardship from them. 3. Betterments (taÍsÊniyyÉt), which are neither essentials nor necessities, but they cause human beings to be in better condition in all aspects of their life. The first category is further divided into following sub-types: protection of religion, protection of life, protection of progeny, protection of intellect, and protection of wealth. They are applicable for both Muslims and non-Muslim minorities who live within a majority Muslim society under a Muslim or Islamic government. The following section of this paper discusses protection of these objectives in Islam and their implications for non-Muslim minorities living in a Muslim majority country.